Experimental Bell violations with classical, non-entangled optical fields - Gonzales, J (2018)
CONCYTEC-FONDECYT (Grant-Nr. 233-2015); CONCYTEC-FONDECYT (Grant-Nr. 236-2015); DGI-PUCP (Grant-Nr. 441).